Creatine and pregnancy outcomes, a prospective cohort study in low-risk pregnant women: study protocol - De Guingand, Deborah L; Ellery, Stacey J; Davies-Tuck, Miranda L; Dickinson, Hayley (BMJ open, 2019)
IntroductionThe creatine kinase circuit is central to the regulation of high-energy phosphate metabolism and the maintenance of cellular energy turnover. This circuit is fuelled by creatine, an amino acid derivative that can be obtained from a diet containing animal products, and by synthesis in the body de novo. A recent retrospective study conducted in a cohort of 287 pregnant women determined that maternal excreted levels of creatine may be associated with fetal growth. This prospective study aims to overcome some of the limitations associated with the previous study and thoroughly characterise creatine homeostasis throughout gestation in a low-risk pregnant population.Methods and analysisThis study is recruiting women with a singleton low-risk pregnancy who are attending Monash Health, in Melbourne, Australia. Maternal blood and urine samples, along with dietary surveys, are collected at five time points during pregnancy and then at delivery. Cord blood and placenta (including membranes and cord) are collected at birth. A biobank of tissue samples for future research is being established. Primary outcome measures will include creatine, creatine kinase and associated metabolites in antenatal bloods and urine, cord bloods and placenta, along with molecular analysis of the creatine transporter (SLC6A8) and synthesising enzymes L - arginine:glycine amidinotransferase (AGAT) and guanidinoacetate methyltransferase (GAMT) in placental tissues. Secondary outcome measures include dietary protein intake over pregnancy and any associations with maternal creatine, pregnancy events and birth outcomes.Ethics and disseminationEthical approval was granted in August 2015 from Monash Health (Ref: 14140B) and Monash University (Ref: 7785). Study outcomes will be disseminated at international conferences and published in peer-reviewed scientific journals.Trial registration numberACTRN12618001558213; Pre-results.